Driving stroke quality improvement at scale in EDs across a nationwide network of hospitals: strategies and interventions. Issue 7 (22nd June 2019) - Shpak, Max; Korwek, Kimberly; Nadasdy, Zoltan; Ramakrishnan, Anurekha; Cowperthwaite, Matthew; Ankrom, Kristen; Jennings, Jon; Moody, Ashley; Orndorff, Kevin; Fanale, Christopher
Abstract : Objectives: Reducing the treatment time while increasing the proportion of eligible stroke patients who receive intravenous tissue plasminogen activator (tPA) has been a priority for many quality improvement efforts. Recent studies have primarily focused on identifying interventions that reduce door-to-needle (DTN) time, while comparatively little has been done to determine whether these interventions also improve tPA rates. Methods: In order to investigate interventions related to process improvements, an electronic dashboard serving as a stroke performance tool was implemented to store and retrieve patient outcome data. These data were used to study the efficacy of interventions designed to facilitate triage of stroke patients in the ED, and determine the individual interventions associated with the most significant improvements in the fraction of patients receiving tPA and in reducing the DTN time. Stroke performance data from the dashboard collected over a 2-year period (2015–2017) from 89 US hospitals were analysed with respect to interventions implemented by individual facilities, as verified by a hospital survey. Results: A statistically significant association was found between increases in the fraction of patients receiving tPA and reductions in DTN time over the study period. These improvements in outcomes were most strongly associated with process interventions that allocate stroke-specific physical and human resources in the ED, most notably a designated emergency room space for stroke, and with workflows that decrease the time to key checkpoints for determining a patient's eligibility for tPA. Conclusions: Data from the stroke performance tool was leveraged to identify the programmes and process interventions that lead to improved patient outcomes and allow EDs to better prioritise process interventions and resources.